High-Fat Diets Led to OTU-Level Shifts in Fecal Samples of Healthy Adult Dogs - Kilburn, Logan R.; Koester, Lucas R.; Schmitz-Esser, Stephan; Serão, Nick V. L.; Rossoni Serão, Mariana C. (Frontiers in Microbiology, 2020)
High fat diets have been reported to negatively affect the microbiota in both mice and humans. However, there is a lack of studies in canine models. The variation among the gastrointestinal (GI) tract anatomy/physiology and typical diet compositions of these animal species may lead to vastly different results. Due to the large inclusion rate of dietary fat in pet food, it is critical to understand its effects in a canine model. Therefore, the study objective was to report the effects of high fat, low carbohydrate diets on the fecal microbiota in healthy adult dogs. Eight adult beagles were randomly assigned to one of four dietary treatments within each 15-day period of a replicated 4x4 Latin Square design. Diets contained 32% (T1), 37% (T2), 42% (T3), and 47% (T4) fat. T2, T3, and T4 were created by adding increasing levels of canola oil to T1, a commercially manufactured canned canine diet, which served as the control diet. Fresh fecal samples were collected during the last five days of each period for microbial analysis. DNA was extracted from fecal samples and paired-end 16S rRNA gene amplicon sequencing was performed using the Illumina MiSeq platform. When comparing whole microbial communities using PERMANOVA, no significant differences were observed among treatments (P = 0.735). Individual OTUs were analyzed using the GLIMMIX procedure of SAS with fixed effects of diet and room, and the random effects of period and animal. Out of the 100 most abundant individual OTUs, 36 showed significant differences in abundance based on treatment (q < 0.05). Overall, OTUs assigned to genera related to fat digestion increased while OTUs assigned to genera involved in carbohydrate digestion decreased. In conclusion, the microbial community adapted to dietary intervention without jeopardizing the health of the animals, evaluated by body condition score, fecal characteristics, and blood parameters.